Potential Benefits of Debates: Perceptions of EFL Pre-Service Teachers - Rosas-Maldonado, Maritza; Bascuñán, Daniela; Martin, Annjeanette (Lenguas Modernas, 2020)
This qualitative case study explores the perceptions of EFL pre-service teachers regarding the potential benefits of using in-class debates. 17 wtudents of an English Teacher Education Programme at a private Chilean university were interviewed via focus groups conducted after each debate activity. The results reveal that debates are considered to promote academic, linguistic, and soft skills and to trigger positive feelings and reactions among students. Although these findings confirm previous studies, there was a unique benefit that emerged from this group of students who also considered debates as a pedagogical tool for their future teaching practice. This new finding emphasises the relevance of incorporating debates in the training of future English teachers.